Media Exposure of National Health Insurance Program Among University Student - Moh Zaenal Abidin Eko Putro; Ade Haryani; Hanif Firdaus (Jurnalistik dan Media, 2024)
Participation number of youth student to national health insurance program is low. Nationally, it is expected that there are 127 million workers including youth people. The eligible number of workers which potentially participate in BPJS of Employment is 86 million. According to the data, 43 million workers have joined BPJS of Employment. However, those members that actively pay monthly insurance reachc only 24,6 million. By implementing a qualitative approach, this research aims at seeking to what extent information that dealing with National Health Insurance of Social Security Organizing Body is accepted and understood by university student. Six university students were interviewed to collect the primary data. The research result is that knowledge, understanding and perception of BPJS is unsimilar among university students resulting from the various type of formats, channels as well as contents the program’s information they have being exposed.